WASTE: DOLZARB AS A PROBLEM - Sherko'zieva G. F.; Toshpulatov B. M.; Fayziev O' (Bright Mind Publishing, 2026)
In this article, solid household waste, which is one of the main sources of pollution of the environment, especially the soil, their accumulation norms and temporary storage issues are highlighted. It has been studied that temporary waste storage containers in cities depend on several factors, in particular, population: jThe total number of waste collection sites is 118, of which 49 are with houses, and 69 are without houses. The number of waste collection containers is 275, of which 249 are 1100 l, 15 are 077 l, and the number of multilift containers is 11.
Keywords: Environment, population, waste, urbanization, pollution, container, soil.